Identification of Parasitic Worm Eggs in Cow Feces from Sepang Bay, Lembar District, West Lombok Regency, West Nusa Tenggara - Ahmad Jupri; Nina Nurraudatul Jannah (Jurnal Biologi Tropis, 2021)
Cows are one of the ruminant animals and farm animals that have a higher economic value compared to other livestock such as chickens, goats, buffalo and others, so many people build cattle farming businesses. In this case, the health of farm animals is one of the main factors that determine the successful production of cows. The study aims to detect the type of eggs from parasitic worms in cow feces and the degree of infection based on Total Standard (Egg Per Gram). Fecal sampling is done randomly from traditional breeder cows in Teluk Sepang Lembar Subdistrict. The sample number of 10 community cattle farms. Identification of the type of worm was carried out at UPTD Animal Hospital and Veterinary Laboratory of Animal Husbandry and Animal Health Office of West Nusa Tenggara Province. Furthermore, quantitative examination uses the buoyant method (Flotation method) and qualitatively with the Mc. Master method that calculates the number of eggs per gram (EPG) of feces. The results showed 6 negative samples and 4 positive samples infected with parasitic worms,and ÃÂ 2 types of worm eggs of the nematode class namely Trichostrongylus sp. and Chabertia ovina , and 1 species of cestoda class namely Moniezia sp. Based on the standard total EPG (Egg Per Gram) feces it is known that the degree of infection of the type of worm eggs Trichostrongylus sp., Chabertia ovina and Moniezia sp. It is low level.ÃÂ